2016
DOI: 10.1111/jmg.12214
|View full text |Cite
|
Sign up to set email alerts
|

Tectonometamorphic evolution of an intracontinental orogeny inferred from P–T–t–d paths of the metapelites from the Rehamna massif (Morocco)

Abstract: New petrographic and microstructural observations, mineral equilibria modelling and U/Pb (monazite) geochronological studies were carried out to investigate the relationships between deformation and metamorphism across the Rehamna massif (Moroccan Variscan belt). In this area, typical Barrovian (muscovite to staurolite) zones developed in Cambrian to Carboniferous metasedimentary rocks that are distributed around a dome‐like structure. First assemblages are characterized by the presence of locally preserved an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 93 publications
2
24
0
1
Order By: Relevance
“…Michard et al () suggested that HT‐LP metamorphism accompanying this compressive event in the Rehamna and the Jebilet was controlled by an older thermal anomaly in relation with the Late Devonian‐Early Carboniferous intracontinental rifting stage. This hypothesis is also supported by Chopin et al () and Wernert et al () for the Rehamna massif. Our results have further confirmed this model for the Jebilet massif.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Michard et al () suggested that HT‐LP metamorphism accompanying this compressive event in the Rehamna and the Jebilet was controlled by an older thermal anomaly in relation with the Late Devonian‐Early Carboniferous intracontinental rifting stage. This hypothesis is also supported by Chopin et al () and Wernert et al () for the Rehamna massif. Our results have further confirmed this model for the Jebilet massif.…”
Section: Discussionsupporting
confidence: 71%
“…Maps (modified after Michard et al, ; Wernert et al, ) and three‐dimensional idealized model for the evolution of the Moroccan Meseta domain and the Jebilet Massif from the Late Devonian to the Early Permian (see text for discussion). The large gray arrows correspond to the crustal shortening direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regional metamorphism occurs commonly coupled with deformation, which results in several generations of folds and / or shearing at different stages of metamorphism (e.g. Li et al, 2005Li et al, , 2010Wernert et al, 2016). In the Shuixiakou area, three episodes of deformation (D1-D3) were distinguished in the metamorphic complex.…”
Section: Samplementioning
confidence: 99%